Total plasma Nε-(carboxymethyl)lysine and sRAGE levels are inversely associated with a number of metabolic syndrome risk factors in non-diabetic young-to-middle-aged medication-free subjects - Šebeková, Katarína; Krivošíková, Zora; Gajdoš, Martin (Clinical chemistry and laboratory medicine, 2014)
Interaction of advanced glycation end products (AGEs) with their specific cell-surface receptor for AGEs (RAGE) induces production of reactive oxygen species, pro-diabetic, pro-inflammatory, and pro-atherogenic responses. The metabolic syndrome (Metsy) imposes a high risk of development of cardiovascular disease and unequivocally predisposes the non-diabetics to type 2 diabetes mellitus. The aim of the study was to investigate the association between circulating soluble RAGE (sRAGE), N -(carboxymethyl)lysine (CML) or AGE-associated fluorescence of plasma (AGE-Fl) with the number of manifested Metsy risk factors in young-to-middle-aged medication-free non-diabetic subjects. Metsy was classified according to NCEP/ATP III criteria; plasma sRAGE and total CML were determined by ELISA methods and AGE-Fl fluorimetrically. From among 437 participants aged 33±11 years, 58% were females. In total 174 subjects were Metsy risk factors-free, 142 presented one, 59 presented two risk factors, and 62 suffered from Metsy. Plasma sRAGE and CML/albumin levels decreased with increasing number of Metsy risk factors (p<0.01, both), while AGE-Fl/albumin levels remained similar. Multivariate analysis selected waist circumference as a main determinant of plasma sRAGE as well as CML/albumin levels. In young-to-middle-aged non-diabetic medication-free subjects plasma total CML/albumin and sRAGE levels decrease prior to the manifestation of Metsy. With regards to RAGE-mediated CML trapping into adipose tissue inducing dysregulation of pro-inflammatory cytokines, adipokines, and the development of obesity-related insulin resistance, and the potential involvement of sRAGE in feedback regulation of the toxic effects of AGE/RAGE-mediated signaling, this early decline might be of clinical impact in development of type 2 diabetes and its complications.